2017
DOI: 10.1136/jnnp-2016-315324
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and consequences of cerebral small vessel diseases: data from three Asian countries

Abstract: Elderly Asians have a high burden of SVD which was associated with cognitive dysfunction. This suggests that SVD markers should be a potential target for treatment in clinical trials so as to delay progression of cerebrovascular disease and potentially cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(160 citation statements)
references
References 25 publications
9
141
2
8
Order By: Relevance
“…This result may be unexpected since vascular risk factors (a predictor of WMSA) [40,41] are exclusion criteria in ADNI. However, previous studies showed that WMSA burden increases with older age [41,42], and ADNI patients are older than KIDS patients in our study, which could explain our nding of higher WMSA in ADNI. This nding aligns with the recent conceptual framework of biological subtypes of AD [5], i.e., older patients had higher WMSA burden, they more frequently had an A + T + N + pro le, and included a higher proportion of typical and limbic-predominant AD cases.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This result may be unexpected since vascular risk factors (a predictor of WMSA) [40,41] are exclusion criteria in ADNI. However, previous studies showed that WMSA burden increases with older age [41,42], and ADNI patients are older than KIDS patients in our study, which could explain our nding of higher WMSA in ADNI. This nding aligns with the recent conceptual framework of biological subtypes of AD [5], i.e., older patients had higher WMSA burden, they more frequently had an A + T + N + pro le, and included a higher proportion of typical and limbic-predominant AD cases.…”
Section: Discussioncontrasting
confidence: 63%
“…Although using different methods for WMSA could induce some noise in our analysis, we recently showed that both methods are strongly associated with each other [27]. Further, by classifying the output from both methods into high and low WMSA burden, we used a rougher measure that is less in uenced by differences between the two methods and has greater clinical applicability [42].…”
Section: Limitationsmentioning
confidence: 99%
“…Ни для кого не секрет, что АГосновной фактор риска хронической ишемии головного мозга и сосудистых когнитивных нарушений. По разным данным, поражение головного мозга, не вызванное инсультом, встречается у 70-95% пациентов с АГ в зависимости от возраста, пола и критериев включения [27,28]. Вследствие поражения головного мозга на фоне гипертонической болезни формируются нарушения когнитивных функций [29].…”
Section: причины коморбидности хронической боли и артериальной гипертunclassified
“…To date, SVD has been recognized to be the second commonest cause of dementia, gait disturbances, affective disorders and late-onset depression [5]. SVD is becoming a major public health issue in Asian countries especially in China [6].…”
Section: Introductionmentioning
confidence: 99%